Shame, perceived knowledge and satisfaction associated with mental health as predictors of attitude patterns towards help-seeking. (18th July 2013) - Rüsch, N.; Müller, M.; Ajdacic-Gross, V.; Rodgers, S.; Corrigan, P.W.; Rössler, W.
Abstract : Aims: To examine stigma- and knowledge-related barriers to help-seeking among members of the general population. Methods: In a representative survey of young to middle-aged Swiss adults ( n  = 8875), shame about a potential own mental illness, perceived knowledge about and satisfaction with one's mental health, psychiatric symptoms and attitudes towards help-seeking were assessed. Results: A latent profile analysis of all participants yielded two groups with different attitudes towards help-seeking. Relative to the majority, a one-in-four subgroup endorsed more negative attitudes towards seeking professional help, including psychiatric medication, and was characterized by more shame, less perceived knowledge, higher satisfaction with their mental health, younger age, male gender and lower education. Among participants with high symptom levels ( n  = 855), a third subgroup was reluctant to seek help in their private environment and characterized by high symptoms as well as low satisfaction with their mental health. Conclusions: Shame as an emotional proxy of self-stigma as well as poor subjective mental health literacy may be independent barriers to help-seeking. Interventions to increase mental health service use could focus on both variables and on those individuals with more negative views about professional help, in the general public as well as among people with a current mental illness.